Writing an Effective Abstract for a Scientific Paper - Khatri, Bishnu Bahadur (Nepalese Journal of Development and Rural Studies, 2022)
The publication of scientific paper is an integral part of the research communication process and the career in academia. In the course of scholarly writing, writing an abstract for a scientific paper is both a crucial and challenging endeavor; it should be accurately represented succinct summary of an entire document. The paper discusses the basic format with essential key components of a good abstract for a scientific paper writing and provides a basic guidelines for novice researchers and academia. The paper is based on review of scientific paper, extracted systematically from ‘Google Scholar’ search engine by using basic search strategy. In fact, the primary purpose of an abstract writing is to facilitate the communication of key findings with the readers so they can easily and quickly ascertain the gist of an entire work. More importantly, when writing an abstract, the fundamental five key components such as research context and objectives, brief outline of materials and methods, key findings, conclusion and significance/implications should be taken into account to accurately represent the entire paper.